Biomass-derived fiber materials for biomedical applications - Li, Daixiu; Wang, Yilin; Huang, Wenhua; Gong, Haihuan (Frontiers in Materials, 2023)
With the development of sustainable materials, biomass-derived fiber materials have attracted significant research interest because of their excellent performance, cost-effectiveness, and environmental friendliness. Following their extensive use in biomedical applications, biomass-derived fiber materials are now increasingly used in anti-bacterial, skin wound dressings, bone tissue engineering, drug delivery, etc. However, their practical medical applications are still in their infancy, requiring some reference and strategic directions for the future clinical applications of cross-discipline for biomaterials and medicine, which are provided in this review. The sources and characteristics of the different biomass-derived fibers introduced briefly, encompassing polysaccharide fiber and protein fiber two categories. Then, we summarized the common applications of biomass and its derived fibers in the medical field in recent years. Finally, we discuss the application and advantages of three-dimensional printing technology combined with biomass-derived materials in modern medicine for the better understanding of practical applications in biomass-derived fiber materials.